ВОСПРИЯТИЕ УЧИТЕЛЯМИ ИСПОЛЬЗОВАНИЯ ПОДХОДА ПЕРЕВЕРНУТОГО КЛАССА ДЛЯ ФОРМИРОВАНИЯ МЕЖКУЛЬТУРНОЙ-КОММУНИКАТИВНОЙ КОМПЕТЕНТНОСТИ У УЧАЩИХСЯ СРЕДНЕЙ ШКОЛЫ - Тәженбаева, Айдана (Вестник ЗКУ, 2023)
Abstract. Teaching a foreign language contributes to the development of communicative abilities necessary for effective interpersonal and intercultural communication. The teacher should pay close attention not only to the selection of the most effective pedagogical technologies and methods of teaching a foreign language, but also to the peculiarity of their application, taking into account the ethnic heterogeneity of groups of students. In this case, intercultural communication comes to the fore in the educational process as a basic strategy for understanding the culture of other languages. The process of developing the intercultural communicative competence of students will be more effective if the latest information technologies are actively used.  Flipped classroom is one of the suggested technologies. This article examines the perception of teachers on the using flipped classroom approach on formation intercultural-communicative competence among secondary school students. The article describes the results of the survey conducted among secondary school foreign language teachers.